Pengaruh Kompetensi Pedagogical Content Knowledge (PCK) Terhadap Kesiapan Mengajar pada Mahasiswa PPG Calon Guru di UHAMKA (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the effect of Pedagogical Content Knowledge (PCK) on teaching readiness of prospective Teacher Professional Education Program (PPG) students at Prof. Dr. Hamka Muhammadiyah University (UHAMKA). This study uses a quantitative approach with a survey method to PPG students at UHAMKA. the population in this study were PPG Teacher Candidate Class 2 students in 2024 at Muhammadiyah Prof. Dr. Hamka University. For this reason, the sample taken from the population must be truly representative (representative). Researchers conducted research with 2 classes at UHAMKA, namely PGSD 06 and PGSD 05 classes. Based on the test results above, it can be concluded that the results show the value of F count = 14,974 with a significance level of 0.000 <0.05, so there is an influence of the PCK variable (X) on Teaching Readiness (Y). Based on the results of the constant (a) of 66.056 indicates that if PCK is 0 then, the level of teaching readiness is 66.056 while the PCK coefficient is 0.417 positive value. These results can be interpreted that every time there is an increase in PCK by 1 time, the level of teaching readiness increases by 0.417.Based on the test results above, the R correlation value is 0.441 while the R square is 0.195 x 100% = 19.5%. This shows that Teaching Readiness can be influenced by 19.5% by the independent variable, namely Pedagogical Content Knowledge (PCK). While the remaining 80.5% of teacher professionalism is influenced by other variables outside the research model used in this study.